Pencatatan Perkawinan Menurut Perspektif Tokoh Agama Kecamatan Selupu Rejang - Agustian, Linda; Amda, Ahmad Dibul; Ridwan, Rifanto Bin; Elkhairati, Elkhairati (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Abstract:The purpose of this study is to determine the views of the community and religious leaders of the Selupu Rejang area regarding the urgency of marriage registration according to Islamic law and positive law. This type of research is field research using descriptive qualitative research methods and a socio-normative approach with legal theory. The results of this study show that the urgency of marriage registration according to the perspective of religious leaders in Selupu Rejang District is very important for the sustainability of social and state life. The legal status of an unregistered marriage is incorrect in the sense that it must receive legal certainty and recognition from the State. Therefore, it is appropriate between the two that is theologically correct and juridically correct to have the harmony to create a benefit in marriage for the realization of the purpose of marriage. According to article 6 of the Compilation of Islamic Law, marriage has no legal force if it is not recorded, because justified legal acts are followed by legal protection against all consequences arising from such legal acts.